2005
DOI: 10.1074/jbc.m411226200
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Nitric-oxide Synthase and NO Donor Induce Insulin Receptor Substrate-1 Degradation in Skeletal Muscle Cells

Abstract: Chronic inflammation plays an important role in insulin resistance. Inducible nitric-oxide synthase (iNOS), a mediator of inflammation, has been implicated in many human diseases including insulin resistance. However, the molecular mechanisms by which iNOS mediates insulin resistance remain largely unknown. Here we demonstrate that exposure to NO donor or iNOS transfection reduced insulin receptor substrate (IRS)-1 protein expression without altering the mRNA level in cultured skeletal muscle cells. NO donor i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
79
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(92 citation statements)
references
References 74 publications
(67 reference statements)
9
79
1
Order By: Relevance
“…Thirdly, we found that iNOS −/− and DBKO mice exhibited a profound decrease in collagen deposition in Sirius red-stained sections of AT together with a downregulation of Col6a1 and Col6a3, the genes encoding collagen VI, the major component of ECM in rodents. In this sense, the deletion of Col6a3 leads to the improvement in metabolic health in obese, diabetic ob/ob mice 67 , which is in accordance with the improved obese and diabetic phenotype of our DBKO model reported by our group and others 26,68 . Finally, our results showed that iNOS deletion in ob/ob mice significantly reduces circulating levels and AT expression of the alarmin TNC.…”
Section: Discussionsupporting
confidence: 77%
“…Thirdly, we found that iNOS −/− and DBKO mice exhibited a profound decrease in collagen deposition in Sirius red-stained sections of AT together with a downregulation of Col6a1 and Col6a3, the genes encoding collagen VI, the major component of ECM in rodents. In this sense, the deletion of Col6a3 leads to the improvement in metabolic health in obese, diabetic ob/ob mice 67 , which is in accordance with the improved obese and diabetic phenotype of our DBKO model reported by our group and others 26,68 . Finally, our results showed that iNOS deletion in ob/ob mice significantly reduces circulating levels and AT expression of the alarmin TNC.…”
Section: Discussionsupporting
confidence: 77%
“…In combination, these data demonstrated that S- nitrosylation of Akt is a specific post-translational modification that regulates its activity [30]. S-nitrosylation of IRS-1 is associated with its reduced protein levels in muscle, which may be secondary to degradation via the ubiquitinproteasome system [9,14]. Since the IRβ/IRS-1/Akt pathway plays a central role in metabolic actions of insulin in muscle, including stimulation of glucose uptake and glycogen synthesis, downregulation of this pathway in muscle by S-nitrosylation may be an important mechanism of iNOS-induced insulin resistance.…”
Section: Discussionmentioning
confidence: 84%
“…This inhibition has implications in conditions such as diabetes, insulin resistance, and Alzheimer's disease. Increased inflammation and the elevated production of NO have been shown to affect insulin clearance and processing, which contributes to overall insulin resistance [29,30]. Enhanced expression of iNOS as a result of inflammation is a factor in insulin resistance, and depletion of iNOS has been shown to enhance insulin sensitivity [7,8,29].…”
Section: Discussionmentioning
confidence: 99%